Determination of fatty acids composition in Persian Gulf shrimp, Metapenaeus affinis - Eskandari, Soheyl; Bitaab, Mohammad Amir; Abtahi, Behrooz; Ghaffari, Farahnaz; Moeini Namin, Mahnaz; Mosafer Khorjestan, Saeedeh (Archives of Advances in Biosciences, 2014)
The aim of this work was to analyze the fatty acid profile in Persian Gulf shrimp, Metapenaeus affinis that is one of the edible and well-known shrimps and has suitable amount of fatty acids specific polyunsaturated fatty acids (PUFA). It has been reported that, a high dietary consumption of marine n-3 fatty acids may prevent the development of atherosclerosis and thrombosis. The fatty acids profile were analysed in the male and female shrimps. The maximum amount of saturated fatty acids (SFA) was 35.88 percent of total fatty acids in Bandar Abbas (St. A) samples. Highest monounsaturated fatty acids (MUFA) were 19.59% in station C and uppermost of PUFA was in Bushehr samples equal to 47.2 %. The figures of SFA showed significant difference between stations (p<0.05). MUFA hadn’t significantly different (p>0.05) and finally PUFA differed statistically only between station A and B. ω3 and ω9 in station A also had statistically differ with other stations and demonstrate that ω3 lower but ω9 higher than other stations. Difference in percentage of fatty acids among stations may consequence of consuming different nutrients by each group of shrimp.